Centralized and Distributed Consensus in Wireless Network: An Analytical Comparison - Yu, Dachao; Zhang, Lei (2022 IEEE 20th International Conference on Embedded and Ubiquitous Computing (EUC), 2022)
The mission-critical decisions are usually made by a central node in connected autonomous systems enabled by IoT, AI and 5G etc. The reliability of decision-making largely depends on the condition of the central node, which can have unaffordable costs and low scalability in a massive-scale mobility network. Therefore, mission-critical IoT networks have been seeking new methods to achieve the growing reliability and latency requirement of cooperative decision-making. The distributed consensus protocol, which has been widely used in distributed computing systems, can provide robustness to the liveness of mission-critical decisions that may encounter node faults. This article first analytically derives the performance of two distributed consensus protocols: Raft and Hotstuff BFT, with the extra synchronization phases. In the presence of communication failure, the results are compared with the analytically derived performance of a centralized consensus. The comparison indicates the strengths and weaknesses of these consensus mechanisms from the perspective of full consensus reliability and communication latency, which provides guidelines for deploying the appropriate distributed autonomous systems in the future.